Characterizing slope processes along the Piggtind mountain ridge, using 2D InSAR - Sandbakken, Henrik (UiT Norges arktiske universitet, 2021)
Large rock slope deformations potentially evolving into catastrophic rock avalanches pose an eminent threat to the Norwegian society. A comprehensive characterization of their kinematic behavior, progressive slope development, and current deformation rates are thus required for hazard management. Njunnás and Piggtind/Skulvatindane are two adjacent rock slopes located in Troms County, Norway. Both slopes show morphological features diagnostic for rock slope deformations (RSD) and are, therefore, inventoried as unstable mountains by Geological Survey of Norway (NGU). However, a satisfying understanding of the RSDs are currently lacking. On Piggtind/Skulvatindane, the complex deformation morphology including substantial disintegration of rock and the high presence of superficial and periglacial slope processes partially obscure the deeper rock slope deformation. Hence, accomplishing a robust characterization of the RSD is not trivial and requires a detailed categorization of the slope processes. In this study, two-dimensional satellite Interferometric Synthetic Aperture Radar (2D InSAR) is integrated with geomorphological- and structural investigations. By combining overlapping InSAR data obtained from both ascending and descending acquisition geometries, 2D InSAR surface displacements are estimated, allowing for quantification of all components of the displacement in the vertical E-W plane (horizontal, vertical, combined 2D velocity, and dip of combined 2D velocity vector). The 2D InSAR results and geological interpretations are displayed on maps and plotted along topographic profiles, allowing for detailed visualization. Longitudinal variations in velocity and dip of combined 2D velocity vectors highlight a sliding-motion parallel to measured foliation on Njunnás, suggesting that the pre-existing, moderately inclined foliation planes are utilized as the basal rupture surface. A marked reduction in the dip of the combined 2D velocity vectors and increased brittle fracturing is observed in the lower sections of both RSDs, indicating an abrupt transition to a low-inclined basal rupture surface. Hence, both RSDs are classified as compound bi-planar slides. The RSD at Njunnás is interpreted to deform as a coherent single body due to the detected homogeneous 2D InSAR displacement rates in the order of 2–3 mm/yr. Contrary, the RSD at Piggtind/Skulvatindane generally exhibits displacement rates around 10 mm/yr but comprises large spatial variability of differential velocity. Clusters of high velocity (up to 157 mm/yr) have been interpreted to predominantly correspond to displacement of superficial mass-wasting deposits, solifluction features, and a multi-lobate rock glacier complex superimposed on the RSD. These results highlight the advantage of characterizing RSDs and identifying superficial slope processes with a multidisciplinary approach, combining structural geology, geomorphology, and satellite remote sensing. The utilized approach is readily applicable to other RSDs when well covered with two complementary InSAR geometries and can be exploited to attribute a failure mechanism and state-of-activity to all inventoried RSDs at a regional or national scale.